Enhancing Retirement Security Through Waqf-Backed Pension Funds: A Theoretical Perspective On Healthcare And Financial Sustainability - Ubaidillah, Muhammad; Umma, I'ana; Wardhani, Armania Putri (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This article examines the integration of waqf into pension schemes as a sustainable model to improve pension security and access to healthcare for retirees and their beneficiaries. The study investigates the potential of a waqf-based pension model to provide solutions to the financial and social challenges in pension systems. Efficiently managed waqf assets can provide a sustainable funding mechanism, ensuring stable income and healthcare support for retirees while reducing the financial burden on government-managed pension funds. The paper proposes a structured integration model where waqf funds complement pension schemes through defined benefit and defined contribution mechanisms, emphasizing financial sustainability and healthcare access. By balancing waqf management with long-term pension funds, this integration presents a transformative approach to social security, especially in Muslim-majority countries.